1974
DOI: 10.1021/jo00928a023
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of macrocyclic polythiaethers

Abstract: Macrocyclic polythiaethers have been synthesized and some of their properties have been determined. The compounds reported comprise a homologous series containing two, four, or six sulfur atoms in the macrocyclic ring. One example of a five sulfur atom macrocyclic is included. The synthetic methods allow for symmetrical or unsymmetrical bridging of the ring sulfur atoms by ethylene, tri-, tetra-, penta-, and hexamethylene bridges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(33 citation statements)
references
References 3 publications
2
30
1
Order By: Relevance
“…Concerning 1,4-dithiane (2), it should be noted that Ochrymowycz et al had reported long ago [15] its isolation as a byproduct along with 12S4 (1,4,7,10-tetrathiacyclododecane) in the preparation of the 18S6 macrocycle from the reaction of the PETG salt with dibromoethane (Scheme 5, top) and had rationalized it by postulation of an initial chain lengthening to an intermediate terminal monohalide, followed by an intrachain thia displacement, accompanied by a thiolate-assisted C À S bond cleavage and 1,4-dithiane (2) formation. Our system differs by having no halogen-carbon-activated bond.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Concerning 1,4-dithiane (2), it should be noted that Ochrymowycz et al had reported long ago [15] its isolation as a byproduct along with 12S4 (1,4,7,10-tetrathiacyclododecane) in the preparation of the 18S6 macrocycle from the reaction of the PETG salt with dibromoethane (Scheme 5, top) and had rationalized it by postulation of an initial chain lengthening to an intermediate terminal monohalide, followed by an intrachain thia displacement, accompanied by a thiolate-assisted C À S bond cleavage and 1,4-dithiane (2) formation. Our system differs by having no halogen-carbon-activated bond.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…The heteroatoms of the bridges point outwards and do not seem very well suited for the complexation of a cation in the inside of the cages. In Table 2 we list the distances between the bridgeheads (N···N), the sum of the bonding angles (Σ ωN ), and the distance between the centers of the π-systems, either triple bonds (4)(5)(6)(7)(8) or aromatic rings (9, 10). In the latter case each biphenyl ring provides two centers.…”
Section: (B) Spectroscopic and Structural Propertiesmentioning
confidence: 99%
“…Quite some time had to pass until crown thioethers participated in this development [3] because safe and high-yield routes to these species were lacking. Advances in synthetic methodology [4] and safe and general, high-yield routes [5] resulted in strong activity in this field.…”
Section: Introductionmentioning
confidence: 99%
“…However, if a normal base (such as a sodium or potassium salt) was used to create the dithiolate, the reaction yielded none of the desired product. The reason for this was established by Ochrymowycz in 1974 [49]. In attempting to make thiocrown ethers by a similar methodology, he observed interchain cyclization during the reaction of dithiols with dihalides, creating a sulfonium intermediate that replaced the halide as the leaving group for the S N 2 attack.…”
Section: Ligand Synthesismentioning
confidence: 95%